Dynamics of Advocacy and Community Empowerment Stage through the Resettlement Action Plan Program for the Kampung Bayam Community in the Construction of the Jakarta International Stadium Project by PT Jakarta Propertindo (Perseroda) - Hifdzi Mujtahid; Sari Viciawati Machdum (CV. Publikasi Indonesia, 2024)
Kampung Bayam has been included in the development of the Jakarta International Stadium (JIS) area, which has had social and economic impacts on the community. PT Jakarta Propertindo, the area manager, has a social responsibility to implement a Resettlement Action Plan (RAP). This research aims to describe the advocacy dynamics of the Kampung Bayam community in the RAP program, as well as community empowerment in the same program. The research used a qualitative approach with a descriptive research type. Data collection involved in-depth interviews with 18 informants using purposive sampling techniques. The research findings reveal that advocacy for the RAP program was carried out through contextual principles that included information delivery, negotiation, and consensus building. There were plans for community participation through FGD and mentoring activities. Community empowerment in the RAP program was achieved through enabling, empowering, and protecting processes. The community formed organizations such as cooperatives and opened business stalls to promote empowerment. Efforts were also made to increase the capacity of the Kampung Bayam community.